Examining the Impact of the Internet of Things Tourism Industry in Vietnam - Phi, Pham Trinh Hong; Phuong, Le Thi Nam (International Journal of Research and Applied Technology (INJURATECH), 2025)
Internet of Things (IoT) is one of the outstanding achievements of the 4.0 technology revolution. The application of this technology is being used by many industries to improve work efficiency and save costs during operation. The Vietnamese tourism industry is currently gradually applying IoT in its operations, especially after the Covid-19 pandemic. Therefore, this article aims to provide a document to assess the impacts and trends in tourism when applying IoT. This technology helps to thoroughly solve the diverse experiences of the tourism industry in Vietnam. It acts as a thread to sew the pieces of information together to provide tourists with complete and detailed information